2019
DOI: 10.1111/bld.12303
|View full text |Cite
|
Sign up to set email alerts
|

People with learning disabilities and access to mainstream arts and culture: A participatory action research approach

Abstract: Accessible summary• Ten people with learning disabilities were trained to work with a university to carry out research about people with learning disabilities, arts and culture.• They spoke to 82 people with learning disabilities to find out what gets in the way of attending arts and culture activities.• The research found that transport, cost and needing support often got in the way of people being able to go to activities and people needed to feel safe and welcomed when they attend an arts and culture activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Even fewer studies included people with disability as researchers or had reported evidence of consultation with people with disability in the design and conduct of the research. Gratton (2020) trained 10 people with intellectual disabilities and then conducted research with 82 people with disability. These researchers recommended that people with disability should be similarly engaged in consultation on policies and programs that concern them.…”
Section: Resultsmentioning
confidence: 99%
“…Even fewer studies included people with disability as researchers or had reported evidence of consultation with people with disability in the design and conduct of the research. Gratton (2020) trained 10 people with intellectual disabilities and then conducted research with 82 people with disability. These researchers recommended that people with disability should be similarly engaged in consultation on policies and programs that concern them.…”
Section: Resultsmentioning
confidence: 99%
“…For Darke (2003, p. 132) disability art is 'not to be seen as an equal opportunities issue', but as part of a process of re-presenting a more accurate picture of 'society, life, disability and impairment and art itself', and it is based on legitimising the experience of people with disabilities 'as equal within art and all other cultural practices'. While medicalised (Bang and Kim, 2015;Gratton, 2020) and charitable perceptions of disability continue to hamper creation by artists with disabilities (Darke, 2003, p. 133), people with disabilities use cultural interventions in order to subvert and query the meanings given to disability ('tragedy, loss, dependency'), and 'disability culture emerges as a counterculture' (Kuppers, 2003, p. 6). For Hadley and McDonald (2019, p. 2), the growing field of disability art, culture and media studies engages with the stories told about what it means to be disabled in drama, dance, film, literature, media and other artforms, and also with how workers in these industries 'are developing new accounts of what it means to be disabled'.…”
Section: Cultural Participation Of Persons With Disabilities As Trans...mentioning
confidence: 99%
“…Lack of accessible information, transport, and support to reach cultural venues represent further barriers. For example, reports suggest that ongoing barriers include transportation issues, price of tickets, and lack of information and support at venues (Gratton 2020;Shape 2013). Another report suggests that the cost involved and difficulties with travel are obstacles when it comes to attending arts events, museums, or libraries and that people with disabilities are more likely than others to consider that the types of activities available are not of interest or relevant (BritainThinks 2018; see also Swedish Authority for Participation 2016).…”
Section: Barriers and Facilitators To Access: Audiences In Arts Venue...mentioning
confidence: 99%
“…Finally, factors designed to engage visitors, not just to provide technological solutions, can be facilitative of building a sense of community (Hoyt-O'Brien 2013). For people with ID, to feel safe and welcome in mainstream arts and cultural activities was an important facilitator, and social interaction was central to participants' understanding of culture (Gratton 2020).…”
Section: Barriers and Facilitators To Access: Audiences In Arts Venue...mentioning
confidence: 99%